Efficacy of potentiation of shot put performance through pre-activity heavy medicine ball throws - Judge, L. W.; Bellar, D.; Glickman, E. L. (The Journal of Strength and Conditioning Research, 2010)
It has become increasingly prevalent among track and field throw's coaches to utilize heavy implements as part of the pre-activity warm-up in an attempt to enhance shot put performance. Though the trend exists among coaches, little research has been done to test the efficacy of the use of heavy implements for enhancement of athletic performance. To examine the potentiation effect of throwing a heavy medicine ball on subsequent standing shot put performance. The participants were five college-aged female shot putters (age: 20.0 +/- 1.7yrs, ht: 167.2 +/- 10.9cm, wt: 98.5 +/- 23.6kg, best competition shot put performance: 11.2m +/- 1.2). A within subjects design was used to compare the possible potentiation effects of throwing a heavy medicine ball prior to a competition shot put. Participants reported to the gymnasium on four separate occasions. On the first visit, participants became familiar with the technique of the standing shot put throw, and a maximal throw for height with a heavy medicine ball beginning from the ground. On the second through forth visits participants warmed up (~ 15 min of dynamic stretching) and then completed five, maximal effort, standing throws with a competition indoor shot put (4kg). Each attempt was preceded by one of three randomly assigned treatments. The treatments included a maximal throw for height with either an 8kg or 18.2kg medicine ball, or no medicine ball throw (control). The distance for each of the maximal effort shot put attempt was measured. ANOVA (treatment x time) revealed no significant main effect for treatment (F = 1.738, [eta]p = 0.303, p = 0.236) or time (F = 0.784, [eta]p = 0.164, p = 0.552) as well as no significant interaction effects (F = 0.801, [eta]p = 0.167, p = 0.607). Compared to the control (8.5m +/- 1.5), the 8kg (8.2m +/- 1.5) and 18.2kg (8.1m +/- 1.4) treatments produced mean distances that were shorter, though the difference was not significant. In moderately trained female athletes the use of heavy medicine balls as part of the pre-activity warm-up does not enhance exercise performance based upon the data from the present investigation. Though the findings were not significant a trend existed for a reduction in performance with the increased weight of the pre-throw medicine ball. Further research is needed to determine the impact of an athlete's strength and training status on pre-activity protocols utilizing post activation potentiation.